Voice outcomes following reoperative central neck dissection for recurrent/persistent thyroid cancer. (7th July 2015) - Starmer, Heather; Noureldine, Salem I.; Ozgursoy, Ozan B.; Tufano, Ralph P.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis We aimed to assess voice outcomes following reoperative central neck dissection (RCND) to characterize postoperative voice difficulties experienced, determine the natural progression of vocal recovery, and identify risk factors for the development of voice disorders postoperatively. Study Design Prospective cohort study. Methods Consecutive patients with recurrent/persistent thyroid cancer who were deemed appropriate candidates for RCND were eligible for participation in this study. A battery of voice evaluation measures was administered both preoperatively and 2 to 4 weeks postoperatively. Results Twenty consecutive patients were included. Postoperatively, six (30%) new incidents of vocal fold motion impairment (VFMI) were identified, with two (10%) being due to intentional recurrent laryngeal nerve (RLN) transection. On 1‐year follow‐up, two patients had full restoration of vocal fold mobility and four had persistent VFMI. No preoperative voice/laryngeal exam factors were predictive of postoperative VFMI. Clinically relevant change in postoperative Voice Handicap Index score was absent in all patients without VFMI and present in five of six patients with VFMI (P = .0004). Patients with VFMI had significantly poorer overall dysphonia grade, less glottic closure, and elevated jitter in contrast to those individuals without VFMI. Patients with malignant tissue in the remnant thyroid were four times more likely to develop VFMI than those with central neck lymph node metastases alone (P = .06). Conclusion Patients undergoing RCND are at risk for postoperative VFMI, even when the RLN is anatomically preserved, with subsequent impact on quality of life. Presence of malignant disease in the remnant thyroid appears to be the best predictor for postoperative VFMI. Level of Evidence 2b. Laryngoscope, 125:2621–2625, 2015